The Accuracy 0f CT Chest in Determining Between Ground Glass Opacities And Those Caused by Covid-19 And Other Medications - Erum Habib, Muhammad Nabi, Iqbal Ahmad, Muzaffar Shah, Zarlakhta Zahir, Hamid Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Diagnostic ct scanning of the chest is currently being investigated for its ability to distinguish between ground glass opacities (GGO) caused by coronavirus 2019 (COVID-19) and GGO produced by other causes. Place and Duration: From January 2022 until June 2022, I will work as a Radiologist at Qazi Hussain Ahmad Hospital in Nowshera. Methods: This study was cross sectional study carried out at the Qazi Hussain Ahmad Hospital, Nowshera for a period of six months. The overall sample size in the current study was100 non-contrast chest CTs. Eexperienced radiologists analyzed the CT images of the chest after redacting any personal information. laboratory results and the patient's medical history were noted. Results: The participants comprised 46 people with COVID19 and 100 without COVID19 who also had ground glass opacities on chest CT. There was no statistically significant difference in age between the groups (p-value = 0.212). Out of the non-COVID-19 GGO cases, three patients have hypersensitivity pneumonia in 3, eosinophilic pneumonia in 3, interstitial pneumonia in 7, pulmonary pneumonia in 3, pulmonary fibrosis in 7, drug-induced lung damage in 7, pulmonary alveolar hemorrhage in 3, and pulmonary emphysema in 11. Practical implication: This study will provide physician with the data to compare the likelihood that COVID-19 causes ground glass opacities on a chest CT scan versus the likelihood that they are caused by other probable causes Conclusion: Moreover, the specificity of chest CT in differentiating COVID-19 from viral pneumonia is only intermediate, and the specificity of chest CT in distinguishing COVID-19 from other reasons of ground glass opacities is poor. Keywords: CT Chest, Determining, Ground-Glass Opacities, Covid-19, Medications